Elucidation of Functional Roles of Sialic Acids in Cancer Migration - Sun, Huiyan; Zhou, Yi; Jiang, Hongyang; Xu, Ying (Frontiers in Oncology, 2020)
Sialic acids (SA), negatively charged nine-carbon sugars, have long been implicated in cancer metastasis since 1960’s but its detailed functional roles remain largely elusive. We present a computational analysis of transcriptomic data of cancer vs. control tissues of eight types in TCGA, aiming to elucidate the possible reason for the increased production and utilization of SAs in cancer and their driving roles in cancer migration. Our analyses have revealed for all cancer types: (1) the synthesis and deployment enzymes of SAs are persistently up-regulated throughout the progression for all but one cancer type; and (2) gangliosides, of which SAs are part, tend to converge to specific types that allow SAs to pack at high densities on cancer cell surface as a cancer advances. Statistical and modeling analyses suggest that (i) a highly plausible reason for the increased syntheses of SAs is to produce net protons, used for neutralizing the OH- persistently generated by elevated intracellular iron metabolism coupled with chronic inflammation in cancer tissues; (ii) the level of SA accumulation on cancer cell surface strongly correlates with the stage of cancer migration, as well as multiple migration-related characteristics such as altered cell-cell adhesion, mechanical stress, cell protrusion and contraction; and (iii) the pattern of SA deployment correlates with the five-year survival rate of a cancer type. Overall, our study provides strong evidence for that the continuous accumulation of SAs on cancer cell surface gives rise to increasingly stronger cell-cell repulsion due to their negative charges, leading to cell deformation from electrostatic force-induced mechanical compression, which is known to be able to drive cancer cell migration established by recent studies.